2022
DOI: 10.21203/rs.3.rs-1821186/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The composition and structure of the ubiquitous hydrocarbon contamination on van der Waals materials

Abstract: The behavior of single layer van der Waals (vdW) materials is profoundly influenced by the immediate atomic environment at their surface, a prime example being the myriad of emergent properties in artificial heterostructures. Equally significant are adsorbates deposited onto their surface from ambient. While vdW interfaces are well understood, our knowledge regarding the atmospheric contamination is severely limited, even after the last decades of intense research in the field. Here we show that the common amb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Previous studies have pointed to the presence of a self-organized alkane layer on the surface of graphene-like materials, which is formed during a few days of air exposure. 16,19 Further studies showed that the alkane layer adsorbed on the surface of highly oriented pyrolytic graphite remained stable in aqueous electrolyte and led to a reduction in capacitance. 26 So, it is very likely that the alkane molecules are responsible for our results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have pointed to the presence of a self-organized alkane layer on the surface of graphene-like materials, which is formed during a few days of air exposure. 16,19 Further studies showed that the alkane layer adsorbed on the surface of highly oriented pyrolytic graphite remained stable in aqueous electrolyte and led to a reduction in capacitance. 26 So, it is very likely that the alkane molecules are responsible for our results.…”
Section: Resultsmentioning
confidence: 99%
“…The surface of graphene is covered by saturated alkane molecules, which consist of a carbon chain containing 23 carbon atoms. This conguration is inspired by the research conducted by Palinkas et al 19 The electried graphene-alkane/water interfaces were modeled by fully lling the vacuum region with water molecules (the water density of the bulk region was kept close to 1 g cm −3 ). To represent Helmholtz layers in the models, Na atoms were initially placed in the vicinity of both graphene-alkane surfaces, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation